2017
DOI: 10.33012/2017.15164
|View full text |Cite
|
Sign up to set email alerts
|

Robust Navigation In GNSS Degraded Environment Using Graph Optimization

Abstract: Robust navigation in urban environments has received a considerable amount of both academic and commercial interest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…The MM approach was extended within the batch covariance estimation (BCE) framework [5], [22] to enable the estimation of the multi-modal covariance models during optimization. The BCE approach enables the estimation of the multi-modal covariance model through the utilization of variational clustering [23] on the current set of state estimation residuals.…”
Section: Robust Estimationmentioning
confidence: 99%
“…The MM approach was extended within the batch covariance estimation (BCE) framework [5], [22] to enable the estimation of the multi-modal covariance models during optimization. The BCE approach enables the estimation of the multi-modal covariance model through the utilization of variational clustering [23] on the current set of state estimation residuals.…”
Section: Robust Estimationmentioning
confidence: 99%
“…Soloviev has demonstrated that 2D line LIDAR scan matching can be paired with GPS for navigating in environments where GPS navigation alone can be difficult . More recently, these sensors have been combined in Simultaneous Localization and Mapping (SLAM) approaches, most commonly developed for indoor and GPS‐denied navigation. While SLAM techniques alone have the capability of allowing users to navigate by observing environmental changes, long term positioning often suffers from drift and biases.…”
Section: Related Workmentioning
confidence: 99%
“…However, the method relies heavily on the initial guess of the states to further calculate reliable residuals [33]. Similar work is done in [34]. Moreover, the M-estimator algorithm [35] is applied to further enhance robustness against GNSS outliers in [34].…”
Section: Introductionmentioning
confidence: 99%
“…Similar work is done in [34]. Moreover, the M-estimator algorithm [35] is applied to further enhance robustness against GNSS outliers in [34]. The principle of M-estimator in factor graph optimization is to embed the standard error function with an additional robust function, such as Cauchy [36] and Huber [36] functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation